Braverman readings in machine learning : key ideas from inception to current state : International Conference Commemorating the 40th Anniversary of Emmanuil Braverman's Decease, Boston, MA, USA, April 28-30, 2017, invited talks /: key ideas from inception to current state : International Conference Commemorating the 40th Anniversary of Emmanuil Braverman's Decease, Boston, MA, USA, April 28-30, 2017, invited talks. (2018) - Unknown
No abstract available